IKLAN OBAT KESEHATAN DALAM BINTANG BORNEO PADA TAHUN 1930 DI BANJARMASIN - Sari, Redita (Langgong: Jurnal Ilmu Sosial dan Humaniora, 2023)
The health needs of the community are exploited by health service providers by advertising health medicines in the mass media. Advertisements offering health medicines are increasingly widespread in print media, generally they are advertised in the form of classified advertisements (mini advertisements) which are relatively cheap. There are quite a lot of advertisers every day in certain newspapers offering various kinds of health medicines such as medicine for stomach ache, medicine for itching and allergies, medicine for constipation, medicine for shortness of breath and so on. This research uses a case study method with a qualitative approach. The aim is to find out the specifications regarding advertising regulations for health drugs advertised through classified ads in local media in Banjarmasin. The conclusion of this research shows that in the 1930s there were quite a lot of health service places in the city of Banjarmasin so it is not surprising that health drug advertisements have also appeared a lot. That is very good because it improves the welfare of the community.